The Immune Response against Acinetobacter baumannii, an Emerging Pathogen in Nosocomial Infections - García-Patiño, María Guadalupe; García-Contreras, Rodolfo; Licona-Limón, Paula (Frontiers in Immunology, 2017)
Acinetobacter baumannii, is the etiologic agent of a wide range of nosocomial infections, including pneumonia, bacteremia, and skin infections. Over the last 45 years, an alarming increase in the antibiotic resistance of this opportunistic microorganism has been reported, a situation that hinders effective treatments. In order to develop effective therapies against A. baumannii it is crucial to understand the basis of host-bacterium interactions, especially those concerning the immune response of the host. Different innate immune cells such as monocytes, macrophages, dendritic cells (DCs) and natural killer cells (NKs) have been identified as important effectors in the defense against A. baumannii; among them, neutrophils represent a key immune cell indispensable for the control of the infection. Several immune strategies to combat A. baumannii have been identified such as recognition of the bacteria by immune cells through pattern recognition receptors (PRRs), specifically Toll like receptors (TLRs), that trigger bactericidal mechanisms including oxidative burst and cytokine and chemokine production to amplify the immune response against the pathogen. However, a complete picture of the protective immune strategies activated by this bacteria and its potential therapeutic use remains to be determined and explored.